The Influence of Sport Activities on Some Variables among Arab Students at Physical Education Faculty- Yarmouk University - Khaled Al-Zyoud; Mohammad Al-Ali (My University, 2015)
The purpose of the study was to investigate the Influance of sport activities on some variables among Arab students at physical education faculty at Yarmouk University. The survey approach was employed in the study through administrating a questionnaire on a sample consisting of (113) male and female students. The questionnaire consisted of (47) items and distributed on the following domains: social, psychological, moral and health. Results of the study indicated that means scores for the domains ranged between (3.79-4.46) with high estimation degree. Results of the study indicated significant differences at significance level (α≤0.05) in the all domains due to gender, and in favor of females students. And the study indicated no significant differences in all domains due to residence, accept the health domain in favor of residence (1-2) years. The study recommended the need for supporting Arab student’s adjustment to study in physical education faculty, to raise Arab student’s awareness of Jordanian society traditions and customs by coordinating efforts with student’s affairs deanship at Yarmouk University.

هدفت الدراسة للتعرف إلى تأثير الأنشطة الرياضية على بعض المتغيرات للطلبة العرب الوافدين للدراسة في كلية التربية الرياضية - جامعة اليرموك، حيث تم استخدام المنهج المسحي من خلال استبانه طبقت على عينة مكونة من (113) طالب وطالبة، وتكونت الاستبانه من (47) فقرة موزعة على أربعة محاور. (الاجتماعي، والنفسي، والأخلاقي، والصحي). وأظهرت النتائج أن المتوسطات الحسابية للمجالات تراوحت ما بين (3.79-4.46)، كان أعلاه للمجال الصحي وبدرجة مرتفعة وبالمرتبة الأخيرة المجال الأخلاقي وبدرجة مرتفعة، وكشفت الدراسة عن وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤0.05) في جميع مجالات الدراسة تبعاً لمتغير الجنس، ولصالح الإناث. كذلك كشفت الدراسة عن عدم وجود فروق ذات دلالة إحصائية في جميع مجالات الدراسة تبعاً لمتغير مدة الإقامة، عدا المجال الصحي الذي أظهر فروق ذات دلاله إحصائية ولصالح من (سنه إلى سنتين). وأوصت الدراسة بضرورة العمل علي دعم تكيف الطلبة الوافدين للدراسة في كلية التربية الرياضية مع الحياة الجامعية، وتعريف الطلبة الوافدين بثقافة وعادات وتقاليد المجتمع الأردني من خلال التنسيق مع عمادة شؤون الطلبة في جامعة اليرموك.
تأثير الأنشطة الرياضية على بعض المتغيرات للطلبة العرب الوافدين للدراسة في كلية التربية الرياضية - جامعة اليرموك